Gross Morphological Study on Pelvic Limb Bones of Greater Coucal (Centropus sinensis) - Tamilselvan , S.; Chemmalar, S.; Sivagnanam, S. (International Journal of Bio-resource and Stress Management, 2024)
The present study was conducted during the period from February, 2021 to April, 2024 at Department of Veterinary Anatomy, Veterinary College and Research Institute, Theni, Tamil Nadu, India to document the gross morphological features of the pelvic limb bones (femur, patella, tibiotarsus, fibula, tarsometatarsus and digits) of greater coucal (Centropus sinensis). The bones were collected and processed from four numbers of greater coucal. The femur was a long bone with somewhat curved shaft with four surfaces and two borders. The proximal extremity presented with a distinct hemi spherical head and trochanter major. The distal extremity showed a trochlea anteriorly and condyles posteriorly. The tibiotarsus was the longest bone , made up of a shaft and two extremities. The proximal extremity contained two condyles, among which medial being the larger. The distal extremity was consisted of medial small condyle and lateral larger condyles with intercondyloid fossa. The fibula was a reduced long bone with distinct head and rudimentary shaft. The tarsometatarsus in greater coucal was presented with a shaft and two extremities. The proximal extremity of tarsometatarsus was made up of two concave articular facets with sharp margin for articulation with the distal condyles present in the distal extremity of the tibiotarsus. The distal extremity consisted of three trochlea (medial, middle and lateral) and they were separated by two intertrochlear clefts (medial and lateral) representing the fused second, third and fourth metatarsal bone. The number of phalanges in each digit was one more than the number of digits.